2021
DOI: 10.1111/1477-9552.12461
|View full text |Cite
|
Sign up to set email alerts
|

Food prices, processing, and shocks: Evidence from rice and COVID‐19

Abstract: Rice is the staple food for about half of the world's population and mills are the essential processing link between farmers and consumers, making rice milling one of the most important agro‐processing sectors globally. This paper assesses changes in rice and paddy prices, and processing margins during the COVID‐19 pandemic shock through the lens of rice mills in Myanmar. Our data, collected through telephone surveys with a large number of medium‐ and large‐scale rice millers in September 2020, reveal signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
6
0
3
Order By: Relevance
“…In the short term, supply disruptions and increased demand have led to higher retail food prices, although not for all categories (e.g., in the European Union (EU): Akter, 2020). Export restrictions resulted, in turn, in increased world prices for cereals and, in some cases, their products (Goeb et al, 2021). However, certain studies (Food and Agriculture Organization [FAO], 2020; Kowalczyk, 2020;Szajner, 2020) indicate that global prices of some agricultural commodities declined during the pandemic.…”
Section: Abstraktmentioning
confidence: 99%
“…In the short term, supply disruptions and increased demand have led to higher retail food prices, although not for all categories (e.g., in the European Union (EU): Akter, 2020). Export restrictions resulted, in turn, in increased world prices for cereals and, in some cases, their products (Goeb et al, 2021). However, certain studies (Food and Agriculture Organization [FAO], 2020; Kowalczyk, 2020;Szajner, 2020) indicate that global prices of some agricultural commodities declined during the pandemic.…”
Section: Abstraktmentioning
confidence: 99%
“…Coluccia et al (2021) presented that as well as Covid-19 impact was observed in the agri-food demand and whole changes of supply chain activity's reaction depending on the pandemic restrictions of countries, its effects reflected logistics and transportation services so its effects reflected logistics and transportation services. Goeb et al (2021) explained the changes in rice prices, relating to the disruptions of transportation for reaching the consumer.…”
Section: Related Literaturementioning
confidence: 99%
“…M.A.Beyzatlar -E. Yılmaz İzmir İktisat Dergisi / İzmir Journal of Economics Yıl/Year:2022 Cilt/Vol:37 Sayı/No:3 Doi:10.24988/ije.1058303 705 Recent studies in the literature have also revealed that the Covid-19 outbreak causes some important changes in the food supply chain in terms of transportation of goods and services depending on restrictions Chitrakar et al (2021),Coluccia et al (2021),Goeb et al (2021),. Hobbs (2020),Singh et al.…”
mentioning
confidence: 99%
“…The channels through which the pandemic affects food and nutrition security comprise all four pillars of food security. Food availability and stability are affected by a lack of workers [16], delays in agricultural work [17], an increase in the price of food and materials [18][19][20][21], and trade restrictions [22]. Moreover, major threats to food access and utilization posed by COVID-19 are the loss of household income, reduced purchasing power [23][24][25], and supply chain disruptions caused by lockdown measures [26][27][28].…”
Section: Introductionmentioning
confidence: 99%